Why do emerging markets liberalize capital outflow controls? Fiscal versus net capital flow concerns - Joshua Aizenman; Gurnain Kaur Pasricha (Bank of Canada, 2013)
In this paper, we provide empirical evidence on the factors that motivated emerging economies to change their capital outflow controls in recent decades. Liberalization of capital outflow controls can allow emerging-market economies (EMEs) to reduce net capital inflow (NKI) pressures, but may cost their governments the fiscal revenues that external financial repression generates. Our results indicate that external repression revenues in EMEs declined substantially in the 2000s compared with the 1980s. In line with this decline in external repression revenues and their growth accelerations in the 2000s, concerns related to net capital inflows took predominance over fiscal concerns in the decisions to liberalize capital outflow controls. Overheating and foreign exchange valuation concerns arising from NKI pressures were important, but so were financial stability concerns and concerns about macroeconomic volatility. Emerging markets facing high volatility in net capital inflows and higher short-term balance-sheet exposures liberalized outflows less. Countries eased outflows more in response to higher appreciation pressures in the exchange market, stock market appreciation, real exchange rate volatility, net capital inflows and accumulation of reserves.
Keywords: F32; G15; 330; Debt Management; Financial system regulation and policies; International topics; Recent economic and financial developments